A "double-sided tape" modifier bridging the TiO2/perovskite buried interface for efficient and stable all-inorganic perovskite solar cells. Issue 12 (22nd February 2022) - Ti, Junjie; Zhu, Jingwei; He, Benlin; Zong, Zhihao; Yao, Xinpeng; Tui, Rui; Huang, Hao; Chen, Cong; Chen, Haiyan; Duan, Yanyan; Tang, Qunwei
Abstract : By passivating defects, forming perfect contact and band matching at buried interface and high-quality perovskite film, the DAP "double-sided tape" modification helps the CsPbBr3 PSCs obtain a best PCE of 10.31% and excellent moisture-heat tolerance. Abstract : The carrier recombination loss induced by defects, imperfect contact and energy level barriers at the buried interface severely restricts the greater advancement of comprehensive performance of perovskite solar cells (PSCs). Herein, a versatile inorganic ammonium salt of diammonium hydrogen phosphate (DAP) is exploited as a "double-sided tape" modifier to be deposited at the TiO2 /perovskite buried interface, which not only passivates the surface defects of TiO2 and perovskite layers and simultaneously bridges the two films via the chemical reactions of hydrogen phosphate anions and ammonium cations in DAP with TiO2 and CsPbBr3 perovskite, respectively, but also ameliorates the interface contact and energy level alignment. Moreover, a higher quality perovskite film with fewer grain boundaries and defects is tightly formed on the DAP modified TiO2 layer arising from its lower wettability. Consequently, a substantially improved charge transport and extraction and minimized charge recombination are achieved in DAP tailored all-inorganic hole transport layer-free CsPbBr3 PSCs, yielding a power conversion efficiency as high as 10.31% with an impressive open-circuit voltage of 1.621 V, which is highly increased compared to 7.58% for the control device. Furthermore, the optimized device free of encapsulation exhibits a superior long-term stability after exposure to an air atmosphere at 85 °C with 85% RH over 720 h.